2009
DOI: 10.1515/jgt.2008.088
|View full text |Cite
|
Sign up to set email alerts
|

Complete homology and related dimensions of groups

Abstract: Abstract. In 1992, Goichot introduced a complete homology theory for arbitrary groups developed by Vogel. In 1998, Triulzi investigated another complete homology theory using the satellite approach invented by Mislin. These developments provide the motivation to find a new invariant ichd G of a group G, which is related to complete homology theories. We investigate its properties and related questions. In particular, using this invariant, we show that Triulzi complete homology is isomorphic to Vogel-Goichot co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In [18,Proposition 5.4] the author claimed that for any group G, sfli G = silf G if both are finite. Soon after [18] was published, the author realised that there is an incorrect argument in the proof of [18,Proposition 5.4] even though sfli G ≤ silf G is true. Asadollahi et al showed in [2,Theorem 3.7] that sfli G = silf G provided that ZG is coherent.…”
Section: Appendixmentioning
confidence: 99%
See 3 more Smart Citations
“…In [18,Proposition 5.4] the author claimed that for any group G, sfli G = silf G if both are finite. Soon after [18] was published, the author realised that there is an incorrect argument in the proof of [18,Proposition 5.4] even though sfli G ≤ silf G is true. Asadollahi et al showed in [2,Theorem 3.7] that sfli G = silf G provided that ZG is coherent.…”
Section: Appendixmentioning
confidence: 99%
“…Asadollahi et al showed in [2,Theorem 3.7] that sfli G = silf G provided that ZG is coherent. Thus [18, Question B] cannot be proved by the argument in [18,Question B]. However, Emmanouil showed in [10] that [18,Question B] has a positive answer for any group G.…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations